Muscle dysmorphia: Risk may be influenced by goals of the weightlifter - Skemp, K. M.; Mikat, R. P.; Schenck, K. P.; Kramer, N. A. (The Journal of Strength and Conditioning Research, 2013)
Athletes with muscle dysmorphia suffer from constant dissatisfaction with body size and shape because they perceive themselves as smaller and less muscular than they actually are. There may be discrepancies among the various subgroups within the weightlifting community in regards to vulnerability and susceptibility to the development of MD. The purpose of this study, therefore, was to examine and compare MD symptomology between male and female, competitive and noncompetitive, and appearance-related and performance-related weightlifters. The MD assessments were made with the muscle dysmorphia inventory (MDI). The participants included 85 competitive (55 men and 30 women) and 48 noncompetitive (24 men and 24 women) weight training athletes. Each group included athletes with a primary focus on appearance enhancement or performance enhancement. Factorial analyses of variance were used to measure differences between each group on all MDI subscales. The results showed that men scored significantly higher than did women on the supplement (p = 0.006), physique protection (p = 0.039), and body size and symmetry subscales (p < 0.001). Competitive athletes scored significantly higher than noncompetitive athletes did on diet (p < 0.001), supplement (p < 0.001), exercise dependence (p < 0.001), and body size and symmetry (p = 0.002) subscales. Finally, the athletes focused on appearance enhancement scored significantly higher than athletes focused on performance enhancement on all 6 subscales (p < 0.01). Coaches and health and fitness professionals should understand that the goals of athletes in regard to weight training can influence susceptibility to development of MD symptoms. Knowing that athletes who engage in weight training to enhance appearance may exhibit greater behavioral characteristics than those athletes who do not may be helpful so they may be able to identify, prevent, and reverse MD in the athletes they serve.